2007
DOI: 10.1016/j.dnarep.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Role of MGMT in protecting against cyclophosphamide-induced toxicity in cells and animals

Abstract: O(6)-Methylguanine-DNA methyltransferase (MGMT) is a DNA repair protein that protects cells from the biological consequences of alkylating agents by removing alkyl groups from the O(6)-position of guanine. Cyclophosphamide and ifosfamide are oxazaphosphorines used clinically to treat a wide variety of cancers; however, the role of MGMT in recognizing DNA damage induced by these agents is unclear. In vitro evidence suggests that MGMT may protect against the urotoxic oxazaphosphorine metabolite, acrolein. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 84 publications
1
17
0
4
Order By: Relevance
“…The presence of AGT renders E. coli strains more sensitive to killing by chlorambucil (27) but no effect of AGT status on drug sensitivity was seen in a studies of HeLa or CHO cells (25). Clinical studies have also yielded conflicting results on the role of AGT levels in the outcome of therapy with cyclophosphamide [reviewed (24)]. Recently, it was shown that MGMT does not protect against mutations induced by cyclophosphamide in mice (28).…”
Section: -[S-cysteinyl]ethyl]-n-[2-(guan-7-yl)ethyl]methylamine and mentioning
confidence: 99%
“…The presence of AGT renders E. coli strains more sensitive to killing by chlorambucil (27) but no effect of AGT status on drug sensitivity was seen in a studies of HeLa or CHO cells (25). Clinical studies have also yielded conflicting results on the role of AGT levels in the outcome of therapy with cyclophosphamide [reviewed (24)]. Recently, it was shown that MGMT does not protect against mutations induced by cyclophosphamide in mice (28).…”
Section: -[S-cysteinyl]ethyl]-n-[2-(guan-7-yl)ethyl]methylamine and mentioning
confidence: 99%
“…The method used was the study of Sister Chromatid Exchanges (SCEs). IFO is a powerful and effective drug performing exceptionally in anticancer therapy, on the other hand it induces chromatid fragility and genotoxicity even in healthy tissue cells (Chen et al 2007;Hansen et al 2007;Lialiaris et al 2010a). As previously stated, Mesna can help to avoid haemorrhagic cystitis induced following administration of IFO.…”
Section: Introductionmentioning
confidence: 92%
“…Metilasyon ajanları, kloroetilasyon ajanları) DNA, RNA ve protein gibi hücresel moleküllere alkil grupları transfer ederek biyolojik etkilerini ortaya koymaktadırlar. Bu ajanlar; DNA omurgası içindeki fosfodiester gruplarının oksijeni ile birlikte, nükleik asitlerin nitrojen ve oksijeni içeren nükleofilik bölgeleriyle reaksiyona girerler 11 . Metilasyon ve kloroetilasyon ajanlarının her ikisi de bir unimoleküler nükleofilik substitüsyon reaksiyonu (NS1 reaksiyonu) aracılığıyla hücresel makromoleküllere zarar verir ve bu nedenden dolayı onlar DNA'daki oksijen atomlarına doğru güçlü bir elektrofilik afiniteye sahiptirler.…”
Section: O6-mgmt Ile Onarımunclassified
“…Metilasyon ajanlarının hücre DNA'sında oluşturduğu O6-MeG eklentisi, MGMT (O6-metilguanin-DNA-metiltransferaz) isimli bir enzim tarafından tamir edilir ve metilasyon kaldırılır 2,13,16 . MGMT memeli hücre ve dokularında DNA alkilasyon ajanlarının zararlı etkilerine karşı koruyucu bir rol oynamaktadır 11,15 . MGMT molekülü, alkil eklentilerini kendi üzerindeki sistein amino asidine transfer ederek alkilasyonun mutajenik etkisini ortadan kaldırmaktadır 6,7,11 (Şekil3).…”
Section: O6-mgmt Ile Onarımunclassified
See 1 more Smart Citation